Food chemical hazard detection : development and application of new technologies - Wang, Shuo, 1969- (Wiley Blackwell, 2014)
Food chemical safety remains a serious concern to the food industry. Risks such as adulteration, the existenceof toxic and allergenic compounds in foods, and poor regulation of postharvest processing indicate that food chemical safety is not fully guaranteed. With the increasing trend of globalization in the import and export of food products, the importance of employing accurate and reliable analytical instruments to rapidly detect chemical hazards in foods has become paramount. In recent years, many new applications for using a range of analytical methods to detect food chemical hazards have emerged. - Resumé vydavatel
Keywords: bezpečnost potravin; kontaminanty potravin; kontrola potravin; food safety; food contaminants; food quality control; monografie; elektronické knihy; monographs; electronic books